Before the industrial revolution - Cipolla, Carlo M. (London, United Kingdom : Methuen & Co. Ltd., 1976)
The world in which we live and the problems we face would be unintelligible without reference to that grandiose change which we label the Industrial Revolution. In its turn, the Industrial Revolution was but the ultimate phase, the historically coherent outcome of a development which took place in Europe during the first seven centuries of our millenium. The purpose of this book is precisely that of offering an up-to-date, documented synthesis of those human developments from which our world, with its blessings and its evils, eventually emerged. The book addresses itself to both the student and the general reader; although fundamentally focused on social and economic problems, its approach is essentially interdisciplinary. This double ambivalence may help to explain some of its traits.
Chapter One. Demand -- Chapter Two. The Factors of Production -- Chapter Three. Productivity and Production -- Chapter Four. The Urban Revolution: The Communes -- Chapter Five. Population: Trends and Plagues -- Chapter Six. Technology -- Chapter Seven. Enterprise, Credit, and Money -- Chapter Eight. Production, Incomes and Consumption -- Chapter Nine. The Emergence of the Modern Age -- Chapter Ten. The Changing Balance of Economic Power in Europe.
Includes bibliographical references and index.
Keywords: EUROPE -- ECONOMIC CONDITION